Sinergy of Law Enforcement Agencies in Handling Illegal Fishing Cases in Aceh Waters - Ade Irma Suryani Nasution; Annisa Mutia Pranita; Desty Bulandari; Lutvia Resta Setyawati; Panji Suwarno (Kanun Jurnal Ilmu Hukum, 2021)
Illegal fishing cases often occur in waters at the edge of Indonesia. This article is focused on examining and analyzing the synergy between the authorized institutions in the process of monitoring and handling illegal fishing cases that occur in the waters of Aceh province. This study uses a descriptive qualitative research design. The four authorized institutions coordinate the performance of each other to help each other's role to reduce illegal fishing violations in Aceh Province. LANAL Sabang helped mobilize forces to carry out law enforcement at sea from the threat of violations as well as to safeguard marine resources. PSDKP Lampulo is the foundation for supervising marine and fishery resources in Aceh Province. Panglima Laot has more authority in regulating laot customary law and fishing communities in general. DKP Aceh is the axis of the service and movement for the protection and utilization of marine resources in Aceh Province.